HUBUNGAN PERSEPSI SISWA TENTANG SUASANA LINGKUNGAN BELAJAR DIDALAM KELAS TEORI DENGAN HASIL BELAJAR RAB SISWA KELAS X1 SMK NEGERI 1 PADANG - 538-546 , Mikrizal (CIVED, 2015)
Abstract This correlation reasearch are aims to find of relationship between students' perceptions about class environment and financial planning result of student XI class SMK Negeri 1 Padang. The population are students in XI class SMK Negeri 1 Padang students year 2013/2014 which is 97 students. The results showed that there is a relationship between students' perceptions about the atmosphere of the learning environment in the classroom theory with learning out comes financial planning training eye of  class XI student of SMK Negeri 1 Padang. Mean an atmosphere of learning outcomes theoretical training eye financial planning class XI student of  SMK Negeri 1 Padang. This can be seen from the degree of achievement of the respondents in the variable students’ perception about the atmosphere of the learning environment for students of class XI 70.06 %. While the learning outcomes Draft financial planning class XI Building Engineering Department SMK 1 Padang get enough value . This can be seen by the average level of achievement of learning outcomes at 74,96 . While the value ( r ) obtained for 0.630. Then diterminan coefficient obtained from the calculation of the contribution value of 39.69 %. Keywords: Perceptions, The Atmosphere of the Learning Environment and Learning outcomes